Nickel–Alkyl Complexes with a Reactive PNC‐Pincer Ligand. Issue 20 (27th April 2018) - Jongbloed, Linda S.; Vogt, Nicolas; Sandleben, Aaron; de Bruin, Bas; Klein, Axel; van der Vlugt, Jarl Ivar
Abstract : Based on previous work related to the design and application of rigid tridentate phosphine–pyridine–phenyl coordination offered by a PNC‐pincer ligand upon cyclometalation to nickel, the synthesis, spectroscopic and solid state characterization and redox‐reactivity of two Ni II (PNC) complexes featuring either a methyl (2CH3 ) or CF3 co‐ligand (2CF3 ) are described. One‐electron oxidation is proposed to furnish C–C reductive elimination, as deduced from a combined chemical, electrochemical, spectroscopic and computational study. One‐electron reduction results in a ligand‐centered radical anion, as supported by electrochemistry, UV spectroelectrochemistry, EPR spectroscopy, and DFT calculations. This further attenuates the breadth of chemical reactivity offered by such PNC‐pincer ligands. Abstract : Two Ni II (PNC) complexes featuring either a methyl (2CH3 ) or CF3 co‐ligand (2CF3 ) are described. One‐electron oxidation is proposed to furnish C–C reductive elimination, while one‐electron reduction results in a ligand‐centered radical anion. This further attenuates the breadth of chemical reactivity offered by such PNC‐pincer ligands.